The Extent of Alcohol-Related Problems Among College and University Students in Norway Prior to and During the COVID-19 Pandemic - Ove Heradstveit; Ove Heradstveit; Børge Sivertsen; Børge Sivertsen; Børge Sivertsen; Kari-Jussie Lønning; Kari-Jussie Lønning; Jens Christoffer Skogen; Jens Christoffer Skogen; Jens Christoffer Skogen (Frontiers in Public Health, 2022)
AimTo provide estimates of the distribution of alcohol-related problems in a national sample of college and university students in 2021, i.e., during the COVID-19 pandemic, in comparison with pre-pandemic data from 2018.DesignLongitudinal data from linkage of two recent national health surveys from 2018 to 2021.SettingStudents in higher education in Norway (the SHoT-study).Participants8,287 fulltime students (72.5% women, 27.6% men) that were 18 years or more at the time of the first survey in 2018, and 21 years or more at the time of the second survey in 2021.MeasurementsThe Alcohol Use Disorders Identification Test (AUDIT) was used to assess potential alcohol-related problems.Findings37.0% of male students and 24.1% of female students reported either risky, harmful, or dependent alcohol use in 2021, compared with 55.0% of male students and 43.6% of female students in 2018. This decrease in alcohol-related problems was most pronounced for dependent alcohol use, where we observed a 57% relative reduction among male students (from 3.5% in 2018 to 1.5% in 2021) and a 64% relative reduction among female students (from 1.4% in 2018 to 0.5% in 2021).ConclusionsThe present study demonstrated a sharp decline in alcohol-related problems among students during the COVID-19 pandemic, that were present across gender, age groups, and geographical study locations. Universal preventive measures to limit students' alcohol use should be considered when restrictions related to the pandemic is lifted.